What factors are perceived to influence consideration of IFRS adoption by Vietnamese policymakers? - Phan, Duc Hong Thi (The journal of contemporary issues in business and government, 2014)
International Financial Reporting Standards (IFRS) developed by the International Accounting Standards Board (IASB) are designed to be a single high quality set of global accounting standards. IFRS were originally developed to serve the listed companies in developed capital markets. However, IFRS are increasingly being adopted by emerging economies, disregarding the concerns of the relevance and appropriateness of IFRS to those economies. It has been argued that emerging economies had little choice but to proceed with IFRS upon pressures from external forces. This paper users survey evidence to examine the perceptions of Vietnamese accountants regarding pressures for IFRS adoption on Vietnamese policymakers. Although the Ministry of Finance of Vietnam announced its intention to align Vietnamese accounting legislation with IFRS in November 2013; they have not yet determined the roadmap and pathway for IFRS adoption or convergence. The findings may allow the accounting practitioners, educators, and policy makers to prepare themselves for the change that Vietnam might pursue regarding IFRS.